An Investigation of Political Identity Congruence in the Real Estate Industry - Aiken, K. Damon; Coakley, Brendan; Heinze, Timothy (Business Communication Research and Practice, 2024)
Objectives: Political polarization affects numerous aspects of our lives including attitude formation, communication effectiveness, and an ever-increasing range of consumption behaviors. Research investigating the influence of political partisanship in real estate is limited. This work examines the impact of communicating political identity congruence (PIC; in a real estate sales situation) on consumers’ judgements of the realtor as well as their propensity to conduct business. Methods: An online between-subjects experiment manipulated realtor political party affiliation in a simulated sales situation. The sample was recruited from an online panel (n = 584). The post-exposure survey measured subjects’ judgements of propensity to do business with the realtor, assessments of realtor personality traits, the subjects’ levels of political partisanship, and various demographic data. Results: Findings indicate that (even in contrived online communications) consumers use perceptions of political congruence (or incongruence) to both assess and select (or deny) real estate agents. Effects were further exacerbated by the subjects’ levels of political partisanship; however, in this controlled experimental setting, the effects were primarily seen among Democrat subjects. So, it seems that Republican real estate agents would be less likely to realize returns by indirectly signaling or directly communicating their political ideologies. Conclusions: Communicating PIC positively influences intentions to utilize services as well as assessments of positive personality traits. On the contrary, political identity incongruence can have drastically negative implications for effective sales communications and consumer judgements. More broadly, this work conveys the need for greater recognition of the impact of political biases across consumption contexts. KCI Citation Count: 0